P17 Clinical utility of the tuberculosis Interferon Gamma Test (IGT) in a low incidence area. (2nd December 2011) - Donovan, J T; Yogendran, A; Ramsay, I D; Giles, C; Lee, R W; Scourfield, A T; Doffman, S R
Abstract : Introduction: The clinical utility and cost effectiveness of IGT in low prevalence areas of TB remains unclear. In some clinical settings it has been used to exclude active disease. We describe the experience of IGT in a teaching hospital in a low prevalence area (13/100 000). Methods: We identified individuals who had undergone IGT for any indication from 01 January 2010 to 30 June 2011. Case notes and electronic records were reviewed retrospectively to identify baseline demographics, indications for testing and outcomes where a positive result was identified. Healthcare workers, contacts of TB and new entrants were all screened for latent TB infection (LTBI) with tuberculin skin test and if positive, IGT (as per NICE, 2006). Those on immunosuppressant therapy had IGT alone if a risk factor was identified. In May 2011, there was a change in local contract from QuantiFERON ® TB-Gold In-Tube (QFT), Cellestis International, Australia to T Spot-TB ® (TSp) Oxford Immunotec, Abingdon, UK. Results: 179 cases were identified, 75 (42%) cases had TSp performed and 104 (58%) cases with QFT. There were 5 (3%) indeterminate results (QFT: 4 [4%]; T Spot-TB: 1 [1%]). Two TSp tests could not be processed as there were insufficient white cells (both haemato-oncology patients). Median age was 40 years (IQR 25–60), the majority were from Europe 135 (75%). Other ethnicities included African 17 (9%), South East Asian 14 (8%), Western Pacific 5 (3%), Eastern Mediterranean 4 (2%) and the Americas 4 (2%). 108 (60%) cases were performed to exclude latent TB infection and 71 (40%) to exclude active TB (see Abstract P17 table 1 ). Conclusions: In a low incidence population, approximately one third of new UK entrants, contacts and health-care workers were diagnosed with latent TB, 56% of whom received chemoprophylaxis. The role of IGT to screen for active disease is unclear and requires further investigation. However, it may be of use in patients with uveitis/choroiditis. In those patients with a positive IGT, 80% went on to receive standard therapy for active TB, all of whom clinically improved. However, screening for LTBI was less cost effective for those undergoing biological therapy with only one positive (2%) result.